PROSPECTS FOR LEGAL REGULATION OF COPYRIGHT OBJECTS IN COMPLIANCE WITH INTERNATIONAL STANDARDS - Sopilko, Iryna (Proceedings of National Aviation University (archive), 2016)
Purpose: The purpose of our research is an analysis of ways to improve legal protection of copyright and related rights in accordance with current legislation, major threats and areas for improvement in the context of European integration. Methods: Using the methods of comparison and analysis in conjunction with formal legal determined by the nature and content of the legal protection of copyright. Application of the method of analysis, induction, analogy and formal-legal method allowed to determine the legal means of protection of copyright. The use of formal legal method, comparative analysis and synthesis grounded proposals to address the shortcomings in the current legislation. Results:. In the context of bringing national laws in line with EU legislation, the author considers it appropriate to finalize the draft Law of Ukraine "On Amendments to the Law of Ukraine" On Copyright and Related Rights "(relating to activities of collective management organizations)" in order to protect the proprietary rights of copyright and related rights proprietors. А computer game should be given a definition and included in Article 2 of the Law of Ukraine "On Copyright and Related Rights". In addition, it is necessary to amend other acts governing liability for infringements of rights to this object. Until the definition of a computer game as an object of intellectual property rights is given and the above laws and the Code of Administrative Offences are amended, there is no legal basis to bring any persons to administrative responsibility. Discussion: In this article the author examines special aspects of legal protection of copyright objects in accordance with current legislation. At the same time, in the process of research the author places greater focus on shortcomings in current legislation and proposes the main directions of improvement of current legislation in accordance with international law in the context of protection of copyright objects. Special attention is paid to analysis of the major threats to infringements of copyright and possible solutions of these problems.